(untitled) (Research, Society and Development, 2021)
The main objective of this essay is: “Analysis of the right to happiness for children and adolescents”. With the problem: “What characterizes it and how is the right to joy of children and adolescents is justified?” The following premise was considered “Children are subject to rights and duties, seeking the minimum standard amount to be happy”. The overall goal is to "make an analysis of the right to happiness of the child and adolescent"; the specific objectives are: "Putting the topic under discussion and the laws guaranteed to them in the pursuit of happiness." This task is very important in an individual perspective to show the vulnerability to affect childhood and even pupils at risk situation; for science is a very suitable research to the legal science; It adds to society for warning and by having an essential role in drawing attention to the network of full protection. This is a theoretical qualitative research with a total length of four months.